Halogen-free two-dimensional sheet flame retardant, nylon 66 composite material and preparation method thereof

CN120904365BActive Publication Date: 2026-10-27ZHEJIANG SCI-TECH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510716095.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2026-10-27
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

但是,目前膨胀型阻燃剂存在制备过程复杂、界面相容性差及功能单一等问题

Benefits of technology

[0021](1)本发明基于环境友好型阻燃体系设计原则,采用纳米纤维素、三聚氰胺及氨基三亚甲基磷酸三种绿色原料构建氮磷协同阻燃剂,通过调控分子间相互作用,制得具有独特二维片状结构的阻燃剂;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120904365B_ABST
    Figure CN120904365B_ABST
Patent Text Reader

Abstract

The present application relates to halogen-free two-dimensional sheet flame retardant, nylon 66 composite material and its preparation method, wherein the preparation method of halogen-free two-dimensional sheet flame retardant comprises: (1) dispersing microcrystalline cellulose in sodium periodate aqueous solution, then reacting at 60-80 DEG C for 50-90 min, after the reaction is finished, cooling to room temperature, washing to neutral, drying, and preparing aldehyde nano cellulose; (2) dispersing aldehyde nano cellulose in water, then adding melamine aqueous solution dropwise and reacting at 60-80 DEG C for 0.5-1 h, then adding amino trimethylene phosphoric acid aqueous solution and reacting at 80-90 DEG C for 2-2.5 h, after the reaction is finished, cooling to room temperature, washing, drying, and obtaining halogen-free two-dimensional sheet flame retardant. The two-dimensional sheet flame retardant of the present application has excellent expansion characteristics, two-dimensional sheet structure and interface compatibility, can synergistically improve the flame retardation, anti-dripping, mechanical and heat insulation performance of nylon 66, and has important application value in the field of composite materials, functional textiles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material modification technology, specifically relating to a halogen-free two-dimensional sheet flame retardant, nylon 66 composite material and its preparation method. Background Technology

[0002] Given the flammability and dripping defects of nylon 66, modifying it by adding flame retardants is a common method to achieve flame retardancy in nylon 66.

[0003] Existing flame retardants can be divided into two main categories: halogenated flame retardants and halogen-free flame retardants. Halogenated flame retardants have mostly been banned due to their severe toxicity and pollution. Halogen-free flame retardants include metal hydroxide flame retardants, phosphorus-containing flame retardants, nitrogen-containing flame retardants, and intumescent flame retardants. Among these, while metal oxide flame retardants have some flame-retardant effect, their efficiency is low, usually requiring a high loading, which is detrimental to the mechanical and processing properties of composite materials. Phosphorus-containing flame retardants, due to their red color, the tendency for their plasticizing effect to migrate over time, and the release of toxic phosphine, also limit their application. Nitrogen-containing flame retardants suffer from poor thermal stability and poor interfacial compatibility, leading to poor mechanical properties and ductility of polymer composites. Intumescent flame retardants, mainly composed of nitrogen and phosphorus elements and consisting of acid, gas, and carbon sources, are highly popular due to their high flame-retardant efficiency, low toxicity, and low smoke. However, current intumescent flame retardants suffer from complex preparation processes, poor interfacial compatibility, and limited functionality.

[0004] Therefore, there is an urgent need in this field to develop a new type of halogen-free flame retardant that can improve the flame retardant properties of nylon while also ensuring the stability of other properties and providing more functions to meet actual needs. Summary of the Invention

[0005] Based on the aforementioned shortcomings and deficiencies in the prior art, one of the objectives of this invention is to at least solve one or more of the aforementioned problems in the prior art. In other words, one of the objectives of this invention is to provide a halogen-free two-dimensional sheet flame retardant, a nylon 66 composite material, and a method for preparing the same that meets one or more of the aforementioned requirements.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a halogen-free two-dimensional flake flame retardant includes the following steps:

[0008] (1) Disperse microcrystalline cellulose in an aqueous solution of sodium periodate, and then react at 60-80℃ for 50-90 min. After the reaction is completed, cool to room temperature, wash until neutral, and dry to obtain aldehyde nanocellulose.

[0009] (2) Disperse aldehyde-based nanocellulose in water, then add melamine aqueous solution and react at 60-80℃ for 0.5-1h, then add aminotrimethylene phosphoric acid aqueous solution and react at 80-90℃ for 2-2.5h. After the reaction is completed, cool to room temperature, wash and dry to obtain halogen-free two-dimensional sheet flame retardant.

[0010] As a preferred embodiment, in step (2), the mass ratio of aldehyde-based nanocellulose, melamine, and aminotrimethylene phosphate is 1:(0.5-1.5):(1-4).

[0011] As a preferred embodiment, in step (2), aldehyde-based nanocellulose is dispersed in water, and the mass fraction of aldehyde-based nanocellulose is 0.5-1 wt%.

[0012] As a preferred embodiment, in step (2), the mass fraction of melamine in the melamine aqueous solution is 1-2 wt%.

[0013] As a preferred embodiment, in step (2), the mass fraction of aminotrimethylene phosphoric acid in the aqueous solution of aminotrimethylene phosphoric acid is 8-10 wt%.

[0014] As a preferred embodiment, in step (1), the solid-liquid mass ratio of microcrystalline cellulose to sodium periodate aqueous solution is 1:(90-110), and the concentration of sodium periodate aqueous solution is 0.5-1M.

[0015] The present invention also provides a halogen-free two-dimensional flake flame retardant prepared by the preparation method described in any of the preceding embodiments.

[0016] This invention also provides a method for preparing nylon 66 composite material, comprising:

[0017] Nylon 66 is blended with the halogen-free two-dimensional flake flame retardant described above and then uniformly dispersed in a solvent. The mixture is then coated or molded to obtain a nylon 66 composite material.

[0018] As a preferred embodiment, the amount of the halogen-free two-dimensional flake flame retardant added is 1-25 wt% of nylon 66.

[0019] The present invention also provides a nylon 66 composite material prepared by the preparation method described in any of the preceding embodiments.

[0020] Compared with the prior art, the beneficial effects of this invention are:

[0021] (1) Based on the design principle of environmentally friendly flame retardant system, this invention uses three green raw materials, nanocellulose, melamine and aminotrimethylene phosphoric acid, to construct a nitrogen-phosphorus synergistic flame retardant. By regulating the intermolecular interaction, a flame retardant with a unique two-dimensional sheet structure is obtained.

[0022] (2) Based on the excellent expansion characteristics, two-dimensional sheet structure and interfacial compatibility of the flame retardant of the present invention, the flame retardant, anti-dripping, mechanical and thermal insulation properties of nylon 66 are synergistically improved, and it has important application value in the fields of composite materials and functional textiles.

[0023] (3) The halogen-free two-dimensional sheet flame retardant of the present invention is not only simple to prepare and environmentally friendly, but also has a unique sheet structure that not only helps to improve the interfacial contact area between the flame retardant and nylon 66, but also enhances the interfacial bonding force through hydrogen bonding between the two, significantly improving their compatibility and achieving simultaneous optimization of flame retardant performance and mechanical strength; at the same time, the formed expanded carbon layer gives nylon 66 anti-drip properties, and the two-dimensional sheet structure gives nylon 66 heat insulation properties. Attached Figure Description

[0024] Figure 1 The images shown are SEM images of CNC, C-MEL, and C-MATP, and a TEM image of C-MATP, from Embodiment 1 of the present invention.

[0025] Figure 2 The infrared spectra of CNC, C-MEL, and C-MATP in Embodiment 1 of the present invention are shown below.

[0026] Figure 3 Thermogravimetric analysis (TGA) diagrams of CNC in Example 1 of the present invention and modified nanocellulose in Comparative Examples 1-3 are shown.

[0027] Figure 4 Thermogravimetric analysis (TGA) diagrams of CNC in Example 1 of the present invention and modified nanocellulose in Comparative Examples 4-7 are shown.

[0028] Figure 5 The diagram shows the expansion effect of CNC, C-MEL, and C-MATP in Embodiment 1 of the present invention.

[0029] Figure 6 The mechanical tensile comparison diagrams of the nylon 66 composite film and PA66 in Comparative Examples 8-12 of this invention are shown.

[0030] Figure 7 This is a comparison chart of the LOI (%) of nylon 66 composite films and PA66 in Comparative Examples 8-11 of this invention;

[0031] Figure 8 This is a vertical combustion comparison diagram of the nylon 66 composite film and PA66 of Comparative Example 10 of the present invention.

[0032] Figure 9 This is a comparison diagram of the heat insulation properties of the nylon 66 composite film and PA66 in Comparative Example 10 of this invention. Detailed Implementation

[0033] The following provides further explanation of the halogen-free two-dimensional sheet flame retardant, nylon 66 composite material, and their preparation method of the present invention.

[0034] The method for preparing the halogen-free two-dimensional flake flame retardant of the present invention includes the following steps:

[0035] (1) Disperse microcrystalline cellulose in an aqueous solution of sodium periodate, and then react at 60-80℃ for 50-90 min. After the reaction is completed, cool to room temperature, wash until neutral, and dry to obtain aldehyde nanocellulose.

[0036] The solid-liquid mass ratio of microcrystalline cellulose to sodium periodate aqueous solution can be 1:90, 1:95, 1:100, 1:105, 1:108, 1:110, etc., and the concentration of sodium periodate aqueous solution can be 0.5M, 0.6M, 0.7M, 0.8M, 0.9M, 1M, etc.

[0037] (2) Disperse aldehyde-based nanocellulose in water, then add melamine aqueous solution and react at 60-80℃ for 0.5-1h, then add aminotrimethylene phosphoric acid aqueous solution and react at 80-90℃ for 2-2.5h. After the reaction is completed, cool to room temperature, wash and dry to obtain halogen-free two-dimensional sheet flame retardant.

[0038] The mass ratio of aldehyde-based nanocellulose, melamine, and aminotrimethylene phosphate can be determined according to actual application requirements within the range of 1:(0.5-1.5):(1-4).

[0039] The above-mentioned aldehyde-based nanocellulose is dispersed in water, and the mass fraction of the aldehyde-based nanocellulose can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, etc.

[0040] The mass fraction of melamine in the above-mentioned melamine aqueous solution can be 1 wt%, 1.2 wt%, 1.3 wt%, 1.5 wt%, 1.9 wt%, 2 wt%, etc.;

[0041] The mass fraction of aminotrimethylene phosphoric acid in the above aqueous solution can be 8 wt%, 8.5 wt%, 9.1 wt%, 9.5 wt%, 9.8 wt%, 10 wt%, etc.

[0042] The present invention provides a halogen-free two-dimensional sheet flame retardant prepared by the above preparation method. The two-dimensional sheet structure not only helps to improve the interfacial contact area between the flame retardant and nylon 66, but also enhances the interfacial bonding force through hydrogen bonding between the two, significantly improving their compatibility and achieving simultaneous optimization of flame retardant performance and mechanical strength. At the same time, the formed expanded carbon layer endows nylon 66 with anti-dripping properties, and the two-dimensional sheet structure endows nylon 66 with thermal insulation properties.

[0043] The method for preparing the nylon 66 composite material of the present invention includes:

[0044] Nylon 66 is blended with the halogen-free two-dimensional flake flame retardant described above and then uniformly dispersed in a solvent. The mixture is then coated or molded to obtain a nylon 66 composite material.

[0045] The amount of halogen-free two-dimensional flake flame retardant added is 1-25 wt% of nylon 66, and the specific amount can be determined according to the actual application requirements.

[0046] The present invention provides nylon 66 composite materials, such as nylon 66 composite films and nylon 66 composite blocks, prepared by the above-mentioned method. These materials can be molded into the desired shapes according to the actual application requirements.

[0047] The following specific embodiments further explain and illustrate the halogen-free two-dimensional sheet flame retardant, nylon 66 composite material, and their preparation method of the present invention.

[0048] Example 1:

[0049] The preparation method of the halogen-free two-dimensional flake flame retardant in this embodiment includes the following steps:

[0050] (1) Disperse 2g of microcrystalline cellulose in 200mL of 1M sodium periodate aqueous solution, and then react at 60℃ for 50min. After the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-based nanocellulose CNC.

[0051] (2) Disperse 1g of CNC in 100g of deionized water and stir at room temperature to form a stable CNC suspension;

[0052] 1g of melamine (MEL) was pre-dispersed in 50g of deionized water and stirred at 90℃ until completely dissolved to obtain an aqueous melamine solution.

[0053] Dissolve 2g of aminotrimethylene phosphate (ATMP) in 20g of deionized water and stir at 50°C until completely dissolved to obtain an aqueous solution of aminotrimethylene phosphate.

[0054] Melamine aqueous solution was slowly added to CNC suspension and reacted at 60℃ for 0.5h to obtain intermediate C-MEL; then aminotrimethylene phosphoric acid aqueous solution was added dropwise to intermediate C-MEL system, the temperature was raised to 90℃ and reacted for 2h. After the reaction was completed, it was repeatedly washed with deionized water until neutral, and then freeze-dried for 48 hours to obtain the target product, namely halogen-free two-dimensional flake flame retardant C-MATP.

[0055] like Figure 1As shown, after modification with melamine, the nanocellulose CNC has a spherical structure. After further modification with aminotrimethylene phosphoric acid, the overall morphology exhibits a two-dimensional sheet structure.

[0056] like Figure 2 As shown, the CNC prepared by sodium periodate oxidation was at 1730 cm⁻¹. -1 A distinct characteristic absorption peak appeared at 1557 cm⁻¹, which can be clearly attributed to the stretching vibration mode of the aldehyde group (C=O); comparison with the C-MEL spectrum shows that the C=O characteristic absorption peak completely disappeared after the addition of MEL; furthermore, at 1557 cm⁻¹... -1 and 1028cm -1 Characteristic peaks at 3369 cm⁻¹, attributed to the C=N stretching vibration and CN stretching vibration of the triazine ring, respectively, were observed. This spectral evolution fully verifies the chemical process by which the aldehyde group and the MEL amino group in the CNC molecule form a C=N covalent bond through a Schiff base reaction. In the FTIR spectrum of C-ATMP obtained after adding ATMP, the peak at 3369 cm⁻¹ is... -1 and 3111cm -1 The characteristic absorption peaks at 2651 cm⁻¹ can be attributed to the asymmetric and symmetric stretching vibrations of the NH bond, respectively. It is noteworthy that the peak at 2651 cm⁻¹... -1 The broad absorption band appearing at [value] originates from the stretching vibration of the PO-H group. This signal is significantly enhanced in the ATMP-added system, indicating the activation of the hydroxyl vibration mode of the phosphate ester. From the characteristic spectra of C-ATMP, its P=O double bond stretching vibration is observed at 1154 cm⁻¹. -1 The characteristic absorption peak at 1691 cm⁻¹, and the characteristic absorption peak at 1691 cm⁻¹. -1 and 1407cm -1 The absorption signals at these locations correspond to the asymmetric and symmetric stretching vibration modes of the P-OH group, respectively. Therefore, these absorption bands confirm the successful modification of ATMP.

[0057] Comparative Example 1:

[0058] The preparation method of the modified nanocellulose in this comparative example includes the following steps:

[0059] (1) Disperse 2g of microcrystalline cellulose in 200mL of 1M sodium periodate aqueous solution, and then react at 60℃ for 50min. After the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-based nanocellulose CNC.

[0060] (2) Disperse 1g of CNC in 100g of deionized water and stir at room temperature to form a stable CNC suspension;

[0061] 0.5g of melamine (MEL) was pre-dispersed in 50g of deionized water and stirred at 90℃ until completely dissolved to obtain an aqueous melamine solution.

[0062] Melamine aqueous solution was gradually added dropwise to the CNC suspension under magnetic stirring. The mass ratio of CNC to MEL was 1:0.5. The reaction was carried out at 60℃ for 0.5h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed, and dried to obtain modified nanocellulose C-MEL0.5.

[0063] Comparative Example 2:

[0064] The preparation method of the modified nanocellulose in this comparative example differs from that in Comparative Example 1 in that:

[0065] The mass ratio of CNC to MEL is 1:1, and the other steps are the same as in Comparative Example 1, to obtain modified nanocellulose C-MEL1.

[0066] Comparative Example 3:

[0067] The preparation method of the modified nanocellulose in this comparative example differs from that in Comparative Example 1 in that:

[0068] The mass ratio of CNC to MEL is 1:1.5, and the other steps are the same as in Comparative Example 1, to obtain modified nanocellulose C-MEL1.5.

[0069] Thermogravimetric analysis (TG209 F1, Netzsch) was used to evaluate the thermal stability of the comparative examples 1-3 and the CNC machine. Figure 3 As shown, comparing Comparative Examples 1, 2, and 3, Comparative Example 2 shows better results. The nanocellulose CNC obtained in Example 1 is compared to that in Comparative Example 2, with T... max The temperature increased from 229.7℃ to 232.2℃, and the carbon residue at 700℃ increased from 27.5% to 31.3%.

[0070] Therefore, based on a CNC to MEL mass ratio of 1:1, different masses of aminotrimethylene phosphoric acid aqueous solution were added as control samples.

[0071] Comparative Example 4:

[0072] The preparation method of the halogen-free two-dimensional flake flame retardant in this comparative example differs from that in Example 1 in that the mass ratio of CNC, MEL, and ATMP is 1:1:1.

[0073] Specifically, 1g of aminotrimethylene phosphate (ATMP) was dissolved in 10g of deionized water and stirred at 50°C until completely dissolved to obtain an aqueous solution of aminotrimethylene phosphate; other steps were the same as in the example; halogen-free two-dimensional flake flame retardant C-MATP1 was obtained.

[0074] Comparative Example 5:

[0075] The preparation method of the halogen-free two-dimensional flake flame retardant in this comparative example is the same as that in Example 1.

[0076] Comparative Example 6:

[0077] The preparation method of the halogen-free two-dimensional flake flame retardant in this comparative example differs from that in Example 1 in that the mass ratio of CNC, MEL and ATMP is 1:1:3.

[0078] Specifically, 3g of aminotrimethylene phosphate (ATMP) was dissolved in 30g of deionized water and stirred at 50°C until completely dissolved to obtain an aqueous solution of aminotrimethylene phosphate; other steps were the same as in the example; halogen-free two-dimensional flake flame retardant C-MATP3 was obtained.

[0079] Comparative Example 7:

[0080] The preparation method of the halogen-free two-dimensional flake flame retardant in this comparative example differs from that in Example 1 in that the mass ratio of CNC, MEL and ATMP is 1:1:4.

[0081] Specifically, 4g of aminotrimethylene phosphate (ATMP) was dissolved in 40g of deionized water and stirred at 50°C until completely dissolved to obtain an aqueous solution of aminotrimethylene phosphate; other steps were the same as in the example; halogen-free two-dimensional flake flame retardant C-MATP4 was obtained.

[0082] The thermal stability of the comparative examples 4-7 and the CNC machine was evaluated using a thermogravimetric analyzer (TG209 F1, Netzsch). Figure 4 By comparing Comparative Examples 4, 5, 6, and 7, it can be seen from the figure that Comparative Example 5 showed the best effect. Compared with Comparative Example 5, the T0 of the nanocellulose CNC prepared in Example 1 increased from 197.9℃ to 269.5℃, and the char residue at 700℃ increased from 27.5% to 46.6%. Figure 5 This indicates that the flame retardant C-MATP can form a denser char layer with better expansion properties during combustion, effectively isolating the transmission of heat, combustible gases and smoke, thus achieving a flame retardant effect.

[0083] Therefore, the sample of Comparative Example 5 was used as the optimal sample, namely the flame retardant C-MATP of Example 1, and added to Nylon 66 to improve the mechanical properties and anti-dripping properties of Nylon 66.

[0084] Example 2:

[0085] In this embodiment, nylon 66 composite films with different ratios were prepared:

[0086] In comparison, 4g of nylon 66 was dissolved in 12g of formic acid and stirred at room temperature for 24 hours. After being thoroughly stirred and dissolved, the mixture was coated by a coating tool and the pure nylon 66 film PA-66 was obtained after the formic acid had completely evaporated.

[0087] In this embodiment, 4g of nylon 66 was dissolved in 12g of formic acid, and then 1wt%, 5wt%, 10wt%, and 15wt% of C-MATP flame retardant were added sequentially according to the mass of nylon 66. The mixture was stirred at room temperature for 24 hours. After thorough dispersion, the mixture was coated and molded using a coating tool. A series of samples were obtained after the formic acid had completely evaporated, and were named P / 1C-MATP, P / 5C-MATP, P / 10C-MATP, and P / 15C-MATP, respectively.

[0088] In contrast, Nylon 66 was blended and dispersed with CNC, MEL and ATMP in formic acid, stirred at room temperature for 24 hours, and then coated by a coating tool after thorough dispersion. The sample was obtained after the formic acid had completely evaporated and was named P-CMA.

[0089] The specific comparative ratio and its preparation method are as follows:

[0090] Comparative Example 8:

[0091] The preparation method of the nylon 66 composite film in this comparative example includes:

[0092] 4g of nylon 66 was dissolved in 12g of formic acid, and 0.04g (1wt%) of C-MATP flame retardant was added. The mixture was stirred at room temperature for 24 hours. After thorough dispersion, the mixture was coated using a coating applicator. P / 1C-MATP membrane was obtained after the formic acid had completely evaporated.

[0093] Comparative Example 9:

[0094] The preparation method of the nylon 66 composite film in this comparative example includes:

[0095] 4g of nylon 66 was dissolved in 12g of formic acid, and 0.2g (5wt%) of C-MATP flame retardant was added. The mixture was stirred at room temperature for 24 hours. After thorough dispersion, the mixture was coated using a coating applicator. P / 5C-MATP membrane was obtained after the formic acid had completely evaporated.

[0096] Comparative Example 10:

[0097] The preparation method of the nylon 66 composite film in this comparative example includes:

[0098] 4g of nylon 66 was dissolved in 12g of formic acid, and 0.4g (10wt%) of C-MATP flame retardant was added. The mixture was stirred at room temperature for 24 hours. After thorough dispersion, the mixture was coated using a coating tool and the P / 10C-MATP membrane was obtained after the formic acid had completely evaporated.

[0099] Comparative Example 11:

[0100] The preparation method of the nylon 66 composite film in this comparative example includes:

[0101] 4g of nylon 66 was dissolved in 12g of formic acid, and 0.6g (15%) of C-MATP flame retardant was added. The mixture was stirred at room temperature for 24 hours. After thorough dispersion, the mixture was coated using a coating tool and the P / 15C-MATP membrane was obtained after the formic acid had completely evaporated.

[0102] Comparative Example 12:

[0103] The preparation method of the nylon 66 composite film in this comparative example includes:

[0104] 4g of nylon 66 was mixed and dispersed with CNC, MEL and ATMP (the total mass of CNC, MEL and ATMP was 5% of PA66, and the ratio of the three was 1:1:2) in formic acid. The mixture was stirred at room temperature for 24 hours. After thorough stirring and dispersion, the mixture was coated and molded using a coating tool. The sample was obtained after the formic acid had completely evaporated and was named P-CMA.

[0105] like Figure 6 As shown, the mechanical properties of the direct blend system of nylon 66 with CNC, MEL, and ATMP (P-CMA, Comparative Example 12) are significantly degraded compared to the pure nylon 66 film PA66. However, the nylon 66 composite film system with the introduction of two-dimensional sheet flame retardant exhibits obvious mechanical strengthening characteristics. Furthermore, when the amount of flame retardant added is 5% of the nylon 66 matrix (Comparative Example 9), the material exhibits a synergistic strengthening effect, with its tensile strength increasing by up to 200% compared to the pure nylon 66 film PA66, and its elongation at break also showing a significant increase. These results indicate that the two-dimensional sheet flame retardant prepared in this invention can effectively improve the mechanical properties of the polymer matrix through specific interfacial interactions while achieving high-efficiency flame retardancy, fully demonstrating the significant advantages of two-dimensional sheet flame retardants in simultaneously optimizing flame retardant performance and mechanical strength.

[0106] like Figure 7 As shown, by comparing the LOI (%) values ​​of nylon 66 composite films and pure nylon 66 films PA-66 in proportions 8-11, the introduction of flame retardant C-MATP significantly improved the limiting oxygen index (LOI) of nylon 66, and the LOI values ​​of the modified systems were all higher than those of pure nylon 66.

[0107] like Figure 8As shown, the vertical burning test results indicate that the nylon 66 sample produced dripping during both 10-second sustained burning cycles, significantly increasing the risk of fire spread. In contrast, Comparative Example 10, with the addition of a two-dimensional sheet flame retardant, exhibited superior flame retardant properties: it self-extinguished within 2 seconds after the removal of the ignition source following the first 10-second sustained ignition, and the self-extinguishing time was extended to 24 seconds after the removal of the ignition source following the first 10-second sustained ignition, with no dripping observed throughout the process. Figure 9 It can be seen that this flame-retardant system not only improves the material's anti-dripping performance through physical barrier, but its special two-dimensional layered structure also constructs an efficient thermal barrier, significantly improving the material's thermal insulation performance.

[0108] In summary, the halogen-free two-dimensional sheet flame retardant reinforced nylon 66 composite material of the present invention obtains a flame retardant with a unique two-dimensional sheet structure by regulating the intermolecular interactions; with the excellent expansion characteristics, two-dimensional sheet structure and interfacial compatibility properties of the two-dimensional sheet flame retardant, it synergistically improves the flame retardant, anti-dripping, mechanical and thermal insulation properties of nylon 66.

[0109] Given that there are numerous embodiments of the present invention, and the raw materials and quantities involved can be selected within a limited range according to actual needs, and that the experimental data for each embodiment are extensive and numerous, it is not suitable to list and describe them one by one here. However, the content to be verified and the final conclusions obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be described one by one here.

[0110] The above description is merely a detailed explanation of preferred embodiments and principles of the present invention. For those skilled in the art, there may be changes in specific implementation methods based on the ideas provided by the present invention, and these changes should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a halogen-free two-dimensional flake flame retardant, characterized in that, Includes the following steps: (1) Disperse microcrystalline cellulose in an aqueous solution of sodium periodate, and then react at 60-80℃ for 50-90 min. After the reaction is completed, cool to room temperature, wash until neutral, and dry to obtain aldehyde nanocellulose. (2) Disperse aldehyde-based nanocellulose in water, then add melamine aqueous solution and react at 60-80℃ for 0.5-1h, then add aminotrimethylene phosphoric acid aqueous solution and react at 80-90℃ for 2-2.5h. After the reaction is completed, cool to room temperature, wash and dry to obtain halogen-free two-dimensional sheet flame retardant. In step (2), the mass ratio of aldehyde-based nanocellulose, melamine, and aminotrimethylene phosphate is 1:(0.5-1.5):(1-4). In step (2), aldehyde nanocellulose is dispersed in water, and the mass fraction of aldehyde nanocellulose is 0.5-1wt%.

2. The preparation method according to claim 1, characterized in that, In step (2), the mass fraction of melamine in the melamine aqueous solution is 1-2 wt%.

3. The preparation method according to claim 1, characterized in that, In step (2), the mass fraction of aminotrimethylene phosphoric acid in the aqueous solution of aminotrimethylene phosphoric acid is 8-10 wt%.

4. The preparation method according to any one of claims 1-3, characterized in that, In step (1), the solid-liquid mass ratio of microcrystalline cellulose to sodium periodate aqueous solution is 1g:(90-110)mL, and the concentration of sodium periodate aqueous solution is 0.5-1M.

5. A halogen-free two-dimensional flake flame retardant prepared by the preparation method according to any one of claims 1-4.

6. A method for preparing a nylon 66 composite material, characterized in that, include: Nylon 66 is blended with the halogen-free two-dimensional flake flame retardant as described in claim 5 and then uniformly dispersed in a solvent. The mixture is then coated by scraping or molded to obtain a nylon 66 composite material.

7. The preparation method according to claim 6, characterized in that, The amount of the halogen-free two-dimensional flake flame retardant added is 1-25 wt% of nylon 66.

8. The nylon 66 composite material prepared by the preparation method according to claim 6 or 7.